Sodium alginate hydrogel integrated with type III collagen and mesenchymal stem cell to promote endometrium regeneration and fertility restoration - Shuai, Qizhi; Liang, Yuxiang; Xu, Xinrui; Halbiyat, Zulala; Wang, Xiaowan; Cheng, Jingwen; Liu, Jialing; Huang, Tingjuan; Peng, Zhiwei; Wang, Lei; He, Sheng; Zhao, Hong; et al. (International journal of biological macromolecules, 2023)
A thinner endometrium has been linked to implantation failure, and various therapeutic strategies have been attempted to improve endometrial regeneration, including the use of mesenchymal stem cells (MSCs). However, low survival and retention rates of transplanted stem cells are main obstacles to efficient stem cell therapy in thin endometrium. Collagen type III is a key component of the extracellular matrix, plays a crucial role in promoting cell proliferation and differentiation, and has been identified as the major collagen expressed at the implantation site. Herein, composite alginate hydrogel containing recombinant type III collagen (rCo III) and umbilical cord mesenchymal stem cells are developed. rCo III serves as favorable bioactive molecule, displaying that rCo III administration promotes MSCs proliferation, stemness maintenance and migration. Moreover, rCo III administration enhances cell viability and migration of mouse endometrial stromal cells (ESCs). In a mouse model of thin endometrium, the Alg-rCo III hydrogel loaded with MSCs (MSC/Alg-rCo III) significantly induces endometrial regeneration and fertility enhancement in vivo. Further studies demonstrate that the MSC/Alg-rCo III hydrogel promoted endometrial function recovery partly by regulating mesenchymal-epithelial transition of ESCs. Taken together, the combination of Alg-rCo III hydrogel and MSCs has shown promising results in promoting endometrium regeneration and fertility restoration, and may provide new therapeutic options for endometrial disease. •MSCs/Alg-rCo III has excellent treatment effect on thin endometrium.•Introduction of type III collagen can promote the proliferation and stemness maintenance of MSCs.•Type III collagen promotes cell viability and migration of ESCs.•MSCs/Alg-rCo III hydrogel had therapeutic efficacy on endometrium thickness, glands recovery, angiogenesis and fertility restoration.•MSCs can promote endometrial repair through paracrine regulation of MET in ESCs.